EXPLORING THE PHYTOCHEMICALS POSSESSING ANTIDIABETIC PROPERTY OF MENTHA LONGIFOLIA THROUGH IN SILICO DOCKING APPROACH - S SANTHOSH (International Journal of Pharma and Bio Sciences, 2014)
Diabetes is a chronic metabolic disorder characterized by high blood glucose level in the body due to alteration in carbohydrate metabolism. Prevalence of diabetes is expected to cross 123 million by 2035. Two enzymes, α-amylase and α-glucosidase play a major role in starch digestion. Inhibition of these enzymes results in significant reduction of type 2 diabetes. The plant, Mentha longifolia possess good medicinal values such as, antimicrobial and antioxidant property. It can also be used as an antidiabetic agent. In order to test this hypothesis, the phytochemical constituent of Mentha longifolia was obtained from the previous literature study. In silico docking study was carried out for all the phytochemical against α-amylase and α-glucosidase. Trans-piperitol and menthol are found to be the top two compounds with good binding energy